Analysis of Health Workers' Risk Factors Occupational Health and Safety at the Meuraxa Hospital - Desri Luhonna; Nurjannah Nurjannah; Mudatsir Mudatsir; Said Usman; Irwan Sahputra (Universitas STRADA Indonesia, 2021)
Hospital is a health service institution that provides complete individual health services from inpatient, outpatient and emergency services. This is based on the assumption that the health sector is one of the risky sectors. Injury rates to health workers in this sector are equal to or higher than in other industries generally considered hazardous. These hazards or threats can be classified into biological, physical, ergonomic, chemical, and psychological risks. This research is a quantitative research analytic survey design with cross sectional approach, which aims to determine the analysis of risk factors that most influence on occupational safety and health.The most dominant factor influencing occupational safety and health is the work unit variable in inpatients, namely the inpatient work unit which has an effect of 18.2 times on occupational safety and health.